Review of the application of virtual reality in language education from 2010 to 2020 - Zheng Chunping; Yu Miao; Guo Zhiyan; Liu Hanyong; Gao Mengya; Chai Ching Sing (Journal of China Computer-Assisted Language Learning)
Virtual reality (VR) is an innovative technology that has been applied in language education to improve learners’ motivation, engagement and academic performance. This review study analyses 69 empirical studies on the application of VR in language education. These studies were published by 12 Chinese and international scholarly journals between 2010 and 2020. A coding framework was formulated for conducting a systematic literature review, and content analyses revealed the general publication trends, research methods, research foci and benefits and challenges of VR-supported language education. Among the reviewed studies, English was the main target language, and Second Life was the most widely used VR environment. Most of these studies were conducted among adult language learners, and they adopted mixed types of data to address the research questions. The main research foci include the affordance of VR for enhancing learners’ linguistic and non-linguistic knowledge and competence, learners’ individual differences, teachers’ roles, the nature of interactions, designed features of language-learning tasks and design and development of VR environments for language education. Based on our research findings, we conclude that VR-supported language education has become an emerging research area with the potential for innovating language education. However, there are still challenges to be addressed regarding the optimisation of VR-supported language education.